2022
DOI: 10.1007/s00464-022-09614-y
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic transabdominal preperitoneal (TAPP) approaches to bilateral hernia repair: a multicenter retrospective study using propensity score matching analysis

Abstract: Background Since the introduction of minimally invasive surgery, new techniques like transabdominal preperitoneal (TAPP) repair have progressively gained acceptance for the treatment of groin hernia. Laparoscopic TAPP (LTAPP) is recommended for bilateral repairs. Likewise, the introduction of robotic platforms has promised additional surgical benefits for robotic TAPP (RTAPP), which are yet to be confirmed. This study compared multicenter data obtained from patients undergoing bilateral inguinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Among the included studies, 2 articles [ 16 , 21 ] were randomized controlled trials (RCTs) with a score of 4, indicating high quality. Eight articles [ 12 15 , 17 20 ] were non-randomized controlled studies, and all of them received high-quality ratings based on the Newcastle-Ottawa Scale (NOS). Among these, 2 articles [ 14 , 17 ] scored 8 points, while the remaining 6 articles scored 7 points [ 12 , 13 , 15 , 18 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the included studies, 2 articles [ 16 , 21 ] were randomized controlled trials (RCTs) with a score of 4, indicating high quality. Eight articles [ 12 15 , 17 20 ] were non-randomized controlled studies, and all of them received high-quality ratings based on the Newcastle-Ottawa Scale (NOS). Among these, 2 articles [ 14 , 17 ] scored 8 points, while the remaining 6 articles scored 7 points [ 12 , 13 , 15 , 18 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles [ 12 15 , 17 20 ] were non-randomized controlled studies, and all of them received high-quality ratings based on the Newcastle-Ottawa Scale (NOS). Among these, 2 articles [ 14 , 17 ] scored 8 points, while the remaining 6 articles scored 7 points [ 12 , 13 , 15 , 18 20 ]. The detailed scoring results are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 However, R-TAPP has been noted to provide minimal clinical benefit compared to laparoscopic transabdominal preperitoneal hernia repair (L-TAPP) and open hernia repair. [3][4][5] The RIVAL study, the only randomized control trial, compared the results of R-TAPP with those of L-TAPP, and showed that R-TAPP was associated with longer surgical time, higher cost, and higher frustration for surgeons. 6 In addition, although several metaanalyses have been conducted, none have demonstrated the clinical superiority of R-TAPP.…”
Section: Introductionmentioning
confidence: 99%